PEMBUATAN STARTER UNTUK EKSTRAKSI MINYAK KELAPA MURNI MENGGUNAKAN MIKROBA AMILOLITIK - Naiola, Elidar (BERITA BIOLOGI, 2008)
The thirteen isolates of amylolitic microbes had been tested their ability to extract the oil from " coconut milk" and nine of them could break the emulsion and separated the oil from the water and protein. The aim of this study was to find a starter that can be used for producing the coconut oil by using molase and "gula aer" gewang (Corypha utan Lamk.) palm sugar as the substrates.The result suggest that by using the isolates (ferm. 1 and ferm.2), "gula aer"gewang can be used as a substrate without supplemented by organic nitrogen. The starter prepared with isolate ferm. 1 containing cells of microbe about 10.2 x 10 cell/ml and prepared with ferm.2 about 9.0 - 10.2 x 10 cell/ml. After 4 weeks the amount of the cells decreased to 0.98 x 10 cell/ml and 0.90 x 10cell/ml, respectively, The amount of microbes were stable until 12 weeks.The starter conducted the fermentation processes at 40Â°C for 16 hours and produced the coconut oil. The extracted oil content about 85% saturated fatty acids and 42% of them was lauric acid. Another chemical component of the extracted oil were Iodine numbers, peroxide numbers and free fatty acid (FFA), they were 5.98%, 2.51 Meq/kg and 0.41%, respectively.